Upaya Penanaman Akhlak Siswa Di MA Al-Fatah - Mohammad Ridwan , Mohammad; Mu’arifin , Riyadlul (Amaliyatu Tadris, 2022)
Often ignore their parents even more concerned with playing than learning. And the emergence of many complaints from parents about diffcult children set considering that the moral development of students is currently increasingly concerning. Teachers as an important compenent in education are involved directly in the education process and the formation of students’ character and morals. This research is a field research, and includes qualitative research, based in the discussion including descriptive research using case study approach. Data collection method using observation, interviews, and documentation. The purpose of this study was to determine the offorts to cultivate students’ morals at MA Al- Fatah.